Furazans with Azo Linkages: Stable CHNO Energetic Materials with High Densities, Highly Energetic Performance, and Low Impact and Friction Sensitivities. Issue 35 (21st July 2016) - Qu, Yanyang; Zeng, Qun; Wang, Jun; Ma, Qing; Li, Hongzhen; Li, Haibo; Yang, Guangcheng
Abstract: Various highly energetic azofurazan derivatives were synthesized by simple and efficient chemical routes. These nitrogen‐rich materials were fully characterized by FTIR spectroscopy, elemental analysis, multinuclear NMR spectroscopy, and high‐resolution mass spectrometry. Four of them were further confirmed structurally by single‐crystal X‐ray diffraction. These compounds exhibit high densities, ranging from 1.62 g cm −3 up to a remarkably high 2.12 g cm −3 for nitramine‐substituted azofurazan DDAzF (2 ), which is the highest yet reported for an azofurazan‐based CHNO energetic compound and is a consequence of the formation of strong intermolecular hydrogen‐bonding networks. From the heats of formation, calculated with Gaussian 09, and the experimentally determined densities, the energetic performances (detonation pressure and velocities) of the materials were ascertained with EXPLO5 v6.02. The results suggest that azofurazan derivatives exhibit excellent detonation properties (detonation pressures of 21.8–46.1 GPa and detonation velocities of 6602–10 114 m s −1 ) and relatively low impact and friction sensitivities (6.0–80 J and 80–360 N, respectively). In particular, they have low electrostatic spark sensitivities (0.13–1.05 J). These properties, together with their high nitrogen contents, make them potential candidates as mechanically insensitive energetic materials with high‐explosive performance. Abstract : Mechanically insensitive energetic materials : Various azofurazans (see figure; Y = N or C) were prepared from the parent compound 4‐amino‐ N′ ‐hydroxyfurazan‐3‐carboximiide and their energetic properties were determined. These compounds exhibit high densities, excellent detonation properties, and relatively low impact and friction sensitivities. These properties, together with their high nitrogen contents, make them potential candidates as mechanically insensitive high explosives.